In situ Sr isotope analyses by LA-MC-ICP-MS of igneous apatite and plagioclase from magmatic rocks at the CPGeo-USP - Munoz,Patricio Montecinos (2016)
ABSTRACT: This contribution describes the successful implementation of in situ Sr isotope analyses by LA-MC-ICP-MS at the CPGeo-USP. The choice for an analytical configuration using measurements of half-masses allows the accurate assessment of lanthanide interferences, permitting the determination of Sr isotopes in important REE-rich accessory phases, such as apatite. Likewise, the on-peak-zero method effectively corrects the background contribution (both from Kr and residual Sr contributions from previous ablations) to the signals of the unknown samples. The analytical campaigns resulted in an accuracy, in respect to reference TIMS values, better than 57 ppm (~ ±0.000057 2σ SD) for a modern coral and the Batjberg clinopyroxene which impart significant quality to our data. Similarly, the majority of the stable Sr isotope ratios are close to the accepted values, which also confirms the effectiveness of the method. The achieved accuracy allows the identification and investigation of spatially-controlled isotopic heterogeneities on the micrometric scale in several Sr-rich minerals (apatite, carbonates, plagioclase, and clinopyroxene) with important implications to the understanding of relevant geochemical processes, particularly AFC, source geochemical heterogeneities and magma-mixing.